Migration of Cosmetic Components Into Polyolefins - Laetitia Bolte; Heiner Gers-Barlag; Guido Heinsohn; Rolf Daniels (Advances in Polymer Technology)
Polyolefins such as high-density polyethylene (HDPE), low-density polyethylene (LDPE), and polypropylene (PP) are among the most widely used packaging materials in the cosmetic industry. Since these materials are in direct contact with cosmetic products, various components of the products are adsorbed to the packaging material’s surface and migrate within the amorphous regions of the polyolefin. This migration process, which occurs in both virgin and post-consumer recyclate (PCR) materials, can lead to deformation of the packaging. In this study, different types of virgin and PCR pellets were examined to investigate their interaction with cosmetic products and to understand the factors influencing the migration process. The migration of cosmetic oils was observed in all pellet samples, depending on the composition of the product and environmental conditions. The process was characterized by the weight gain of the plastic pellets and further identified through nuclear magnetic resonance (NMR) and infrared (IR) spectroscopy. Additionally, differential scanning calorimetry (DSC) and gel permeation chromatography (GPC) measurements were performed to analyze the polymer structure. Components with lower molecular weight (MW), high nonpolarity, and elevated temperatures were found to accelerate the migration process. Moreover, migration occurred more slowly from oil-in-water emulsions with larger droplet sizes compared to water-in-oil systems with smaller droplets. Among the different polyolefins, PP demonstrated a higher uptake of migrating components but at a slower migration rate compared to HDPE and LDPE. When comparing virgin and recycled polyolefins, it was observed that migration was consistently slower in virgin materials than in recycled ones. The ability of oils to migrate is influenced by the molecular structure of the polymers: high density, crystallinity, and low levels of branching reduce both the migration speed (MS) and the maximum saturation, as seen in virgin HDPE. In contrast, materials like LDPE, with a less dense polymer structure, exhibited higher MSs and saturation limits. As a control, polyethylene terephthalate (PET) was used, and it showed no migration due to the polymer’s high density.